2007
DOI: 10.1192/apt.bp.106.002501
|View full text |Cite
|
Sign up to set email alerts
|

When a patient dies by suicide: incidence, implications and coping strategies

Abstract: Patient suicide is a relatively common event: 50–70% of consultant psychiatrists and 40–50% of psychiatric trainees have experienced at least one patient suicide. Patient suicide can have significant personal and professional effects on psychiatrists, including increased stress, social withdrawal, disruption to relationships, symptoms of post-traumatic stress disorder and consideration of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
2
27
1
Order By: Relevance
“…International studies have shown that patient suicide is a relatively common experience for consultant psychiatrists, with 50-70% experiencing it at least once. 2 We found the effect on both the personal and professional life of the consultants to be consistent with or greater than previous studies, with up to 97% reporting some disturbance in their personal life. 2,6 Informal support from colleagues was identified by the majority of respondents as the most effective support, which is again reflective of other studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…International studies have shown that patient suicide is a relatively common experience for consultant psychiatrists, with 50-70% experiencing it at least once. 2 We found the effect on both the personal and professional life of the consultants to be consistent with or greater than previous studies, with up to 97% reporting some disturbance in their personal life. 2,6 Informal support from colleagues was identified by the majority of respondents as the most effective support, which is again reflective of other studies.…”
Section: Discussionsupporting
confidence: 89%
“…2 We found the effect on both the personal and professional life of the consultants to be consistent with or greater than previous studies, with up to 97% reporting some disturbance in their personal life. 2,6 Informal support from colleagues was identified by the majority of respondents as the most effective support, which is again reflective of other studies. 6,7 However, the number seeking formal and independent reviews suggests that, although many receive psychological support from family and friends, consultants would also welcome an objective review from a professional view point.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pieta House (www.pieta.ie) offers support, both for those bereaved and those who are feeling suicidal. Patient suicide also affects psychiatrists and other health care staff and can be a substantial source of stress (Foley & Kelly, 2007).…”
Section: Interventions At the Level Of The Individualmentioning
confidence: 99%